Contemporary Marketing Evolves - Migliore, R. Henry; Howard, Nancy C.; Gray, Dana Moore (Journal of Marketing Development and Competitiveness, 2018)
This article encompasses principles of marketing as it relates to the current trends of technology. From the Marketing Plan to Survey Monkey, and the analysis of ACSI to CX on the internet, marketing has fresh nuances that need to be rooted in its time-tested foundation. Measuring customer cost, customer satisfaction, and defining new tools for customer service make this article a noteworthy read. Concluding with social media and ordering capabilities from Alexa; marketing has evolved.